2020
DOI: 10.3390/ncrna6030037
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in Multiple Myeloma Bone Disease Pathophysiology

Abstract: Bone remodeling is uncoupled in the multiple myeloma (MM) bone marrow niche, resulting in enhanced osteoclastogenesis responsible of MM-related bone disease (MMBD). Several studies have disclosed the mechanisms underlying increased osteoclast formation and activity triggered by the various cellular components of the MM bone marrow microenvironment, leading to the identification of novel targets for therapeutic intervention. In this regard, recent attention has been given to non-coding RNA (ncRNA) molecules, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 155 publications
0
13
0
Order By: Relevance
“…Similarly, miR-138 was significatively increased in MM-MSCs compared to HD-MSCs [ 42 ], and inhibition of miR-138 resulted in enhanced osteogenic differentiation of MM-MSCs, being ROCK2, TRPS1, and SULF2 potential miR-138 targets. The expression of other miRNAs has been found upregulated in MM-MSCs (miR-221, miR203a-3p.1, miR-223) or decreased (miR-342, miR-363, or miR-29b) to that of HD-MSCs, modulating the expression of genes involved in osteoblastogenesis (see Raimondi et al [ 43 , 44 ] for reviews).…”
Section: Characterization Of Mesenchymal Stromal Cells In Multiple Myelomamentioning
confidence: 99%
“…Similarly, miR-138 was significatively increased in MM-MSCs compared to HD-MSCs [ 42 ], and inhibition of miR-138 resulted in enhanced osteogenic differentiation of MM-MSCs, being ROCK2, TRPS1, and SULF2 potential miR-138 targets. The expression of other miRNAs has been found upregulated in MM-MSCs (miR-221, miR203a-3p.1, miR-223) or decreased (miR-342, miR-363, or miR-29b) to that of HD-MSCs, modulating the expression of genes involved in osteoblastogenesis (see Raimondi et al [ 43 , 44 ] for reviews).…”
Section: Characterization Of Mesenchymal Stromal Cells In Multiple Myelomamentioning
confidence: 99%
“…Importantly, miR-29b was found to be downregulated in MM-associated dendritic cells (DCs) as compared to normal mature DCs. Enforcement of miR-29b in DCs co-cultured with MM cells counteracted pro-inflammatory pathways, including STAT3, NF-κB, and various cytokine/chemokine signaling networks, and antagonized DC-induced polarization of T helper lymphocytes into Th17 cells [ 66 , 67 ]. An inflammatory BMM, including DCs, has been reported to promote GI in MM, which in turn promotes the arising of mutations responsible for tumor progression, drug resistance, and immune escape [ 68 ].…”
Section: Non-coding Rna Involvement In MM Gimentioning
confidence: 99%
“…Another study found that miR-129-5p, which targeted OBs differentiation markers, was enriched in exosomes from MM patients compared to those from SMM patients, suggesting exosomes may be a useful marker of disease progression (39). Higher expression of exosomal miR-214 detected in osteoporotic patients also suggested exosome's potential as a biomarker for MM bone diseases (34,35). Further validation in other independent MM patient cohorts will explore the potential of circulating exosomal miRNAs to improve the prognostic and risk stratification.…”
Section: Diagnostic and Prognostic Role Of Exosomesmentioning
confidence: 98%
“…Exosomes in the BM have been shown to contribute to this pro-OC microenvironment, resulting in impaired bone formation and MM-related bone disease. Emerging evidence suggests that exosomal ncRNAs play an important role in this regard (34,35).…”
Section: Exosome Impact On Bm Microenvironment Remodelingmentioning
confidence: 99%